Effect of annealing temperature on piezoelectric and mechanical properties of (Bi0.5Na0.5)TiO3–(Bi0.5K0.5)TiO3–BaTiO3 thin films. Issue 1 (January 2016) - Zhan, K.; Su, M.; Han, H.; Xie, S.F.; Zhu, Y.K.; Wang, D.; Cheng, H.B.; Wang, X.Y.
Abstract: Polycrystalline piezoelectric lead-free 85 mol% (Bi0.5 Na0.5 )TiO3 –10 mol% (Bi0.5 K0.5 )TiO3 –5 mol% BaTiO3 (85BNT–10BKT–5BT) thin films were fabricated at different annealing temperatures by a chemical solution deposition method on Pt/Ti/SiO2 /Si substrates. Perovskite phase was achieved during annealing at 650–800 °C. The effect of annealing temperature on piezoelectric and mechanical properties was investigated. The results show that 85BNT–10BKT–5BT thin films annealed at 700 °C exhibit the largest effective d 33 value of 140.4 pm/V, and the highest elastic modulus 142.0 GPa. The optimal properties can be attributed to dense domain and homogenous microstructure. Results show that 85BNT–10BKT–5BT thin films may be a good candidate for lead-free piezoelectric-based micro-electromechanical systems.